Interpersonal communication value in globalizing community - Shebanova, Irina (Creativity Studies, 2010)
The attention in this article is paid to social changes in terms of global information processes and the influence of these changes on the appearance of some new forms of socialization. The transformation period of modern society is in many ways determined by informational processes which are based on modern means of communication and technology. The evolution of these technologies transforms interpersonal communication, it being the vital need and universal value. Tarpasmeninės komunikacijos reikšmė globalizuotoje bendruomenėje Santrauka. Šiame straipsnyje dėmesys sutelkiamas į socialinius pokyčius globaliųjų procesų sąlygomis ir į šių pokyčių įtaką pastebimoms naujoms socializacijos formoms. Moderniosios visuomenės transformacijos laikotarpis yra nulemtas informacinių procesų, kurių pagrindą sudaro modernios komunikacijos priemonės ir technologijos. Šių technologijų evoliucija keičia tarpasmeninę komunikaciją, nulemdama jos esminį poreikį ir universalią vertę. Reikšminiai žodžiai: komunikacija, socializacija, reikšmė, virtualumas.